Modified Munich chain-ladder method - Michael Merz; Mario V. Wüthrich (Risks, 2015)
The Munich chain-ladder method for claims reserving was introduced by Quarg and Mack on an axiomatic basis. We analyze these axioms, and we define a modified Munich chain-ladder method which is based on an explicit stochastic model. This stochastic model then allows us to consider claims prediction and prediction uncertainty for the Munich chain-ladder method in a consistent way.
Keywords: 330; Munich chain-ladder method; claims reserving; prediction uncertainty; mean-square error of prediction; multivariate Gaussian model; paid and incurred claims